"A Yam between Two Rocks": A Comparative Analysis of Disaster Coverage and Geopolitical Dynamics in Nepali and Indian News Reporting of the 2015 Gorkha Earthquake. Issue 3 (November 2021) - Karki, Srijana; Mix, Tamara L.
The devastating Gorkha earthquake, measuring 7.8M on the Richter scale, struck Nepal on April 25, 2015, followed by a major aftershock on May 12, 2015. The earthquakes killed approximately 9, 000 people and injured thousands more, garnering significant media coverage. We employ qualitative content analysis and media framing theories to demonstrate evidence of social construction in the Gorkha earthquake media coverage from two Nepali national and two Indian newspapers. Using a sample of 2, 862 articles published within a year of the earthquake, five major frames: the disaster frame, disaster myths, the therapeutic community frame, recreancy, and international support emerged during the analysis. Our study demonstrates how media coverage reflects current geopolitical dynamics in the region, distinguishing impoverished Nepal from two emerging economic giants, India and China. We contribute to developing literature arguing that media coverage during disasters produces global human life hierarchies. Our study adds a class hierarchy dimension, where tourists are more valuable than locals, and even among tourists, those involved in high-end tourism attract additional media attention.